Tensile yield strength of a single bulk Al0.3CoCrFeNi high entropy alloy can be tuned from 160 MPa to 1800 MPa. (15th March 2019) - Gwalani, Bharat; Gorsse, Stephane; Choudhuri, Deep; Zheng, Yufeng; Mishra, Rajiv S.; Banerjee, Rajarshi
Abstract: While there have been multiple recent reports in the literature of exceptional combinations of yield strength and ductility in high entropy alloys, there have been no reports discussing the extraordinary tunability of the mechanical properties in the same alloy in these systems. This paper shows that the tensile yield-strength of a single Al0.3 CoCrFeNi high entropy alloy (or complex-concentrated alloy), can be enhanced from 160 MPa to over 1800 MPa (1.8 GPa), a 1025% increase, via microstructural engineering enabled by thermo-mechanical processing of the bulk alloy. Such strength variations for the same composition are unprecedented in any other class of alloys. Graphical abstract: Unlabelled Image